Analysis and tracking of animal movements through granulation of temporal domain (GTD) - Rawat, Neelam; S. Sodhi, J.; K. Tyagi, Rajesh (International Journal of Engineering and Technology, 2018)
Thanks to technological advancement in tracking systems, observing the moving patterns of a population is easier now. Capturing the movement patterns is mostly done through various tracking technologies like GPS, GIS etc. but these tracking systems basically require one or more combination of the same, and also, a node or tag to be placed on the moving object. Tracking of movement patterns basically employs a motion model which describes how the image of the object might change in different possible positions of the object during video surveillance. To track multiple objects without deformation during movement, the granulation of temporal domain (GTD) is pro- posed.GTD method is for demodulation of granule adaptation of video image segmentation on the basis of granular computing methodology. In image segmentation, i.e., image granulation through temporal domain, it improves the quality of surveillance important for wild-life protec- tion, and decision making in terms of security.Â Â
Keywords: Video Surveillance; Image Granulation; Background Subtraction; Granular Computing; Temporal and Spatial Domains.